2018
DOI: 10.15761/imm.1000349
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive heart failure: A review of clinical status and meta-analyses of prognostic value of echocardiography and antihypertensive medication

Abstract: Hypertensive heart failure (HHF) is a major public health problem associated with significant morbidity and mortality. Its cardinal characteristics are left ventricular hypertrophy and diastolic dysfunction resulting from the response to biochemical stress imposed on the left ventricle (LV) by a chronic and progressive increase in blood pressure. However, the precise understanding of the nature of HHF has been partial because of its many different terminologies and definitions making comparison and aggregation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 128 publications
(252 reference statements)
0
5
0
Order By: Relevance
“…In many studies, GLS improvement was associated with LVMI reduction ( 10 , 11 , 13 , 26 ), while other researchers found it independently of LVMI changes ( 8 , 14 , 27 ). The present study showed the independent association between GLS improvement and BP reduction, and GLS improvement was earlier than LVMI reduction.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, GLS improvement was associated with LVMI reduction ( 10 , 11 , 13 , 26 ), while other researchers found it independently of LVMI changes ( 8 , 14 , 27 ). The present study showed the independent association between GLS improvement and BP reduction, and GLS improvement was earlier than LVMI reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The present meta-analysis, based on a large sample of hypertensive patients undergoing antihypertensive treatment for a period of at least 6 months or more, revealed several important points that deserve further discussion: LV GLS was significantly improved after antihypertensive treatment, this was also the case for conventional echocardiographic structural and functional (systolic and diastolic) LV parameters, a significant correlation was found between LVMI reduction and GLS improvement in the pooled hypertensive population, no relationship was found between BP reduction and GLS increase after treatment. The improvement of LV systolic/diastolic function and structure (LVMI decrease) after antihypertensive treatment has been widely reported [24,25]. Unfortunately, no consensus exists about the timing of these changes.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, no consensus exists about the timing of these changes. The improvement of LV diastolic function has been reported to precede LVEF and LVMI changes in the course of antihypertensive treatment [24][25][26]. An open question remains the timing of GLS improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous trials have shown that sustained hypertension causes structural, functional, and neurohumoral abnormalities of the heart, involving the ventricular and atrial myocardium as well as the epicardial and intramural coronary arteries, a disease commonly termed hypertensive heart disease (HHD). However, the published definition and classifications of HHD do not always agree, and cardiology societies and scientists have not yet come to a consensus on the terminology of these morpho-functional alterations, using terms such as “hypertensive heart disease” [ 7 , 8 , 9 ], “hypertensive cardiomyopathy” [ 10 ], and “hypertensive heart failure” [ 11 ].…”
Section: Introductionmentioning
confidence: 99%